Ecotourism and sustainability: A bibliometric analysis using R - Nurul Asnitah Sundang; Suddin Lada; Shaierah Gulabdin; Faerozh Madli (Asian Academy of Applied Business, 2023)
Sustainability development in ecotourism is a benchmark for this study which may change over time. This research aims to analyse the relationship between ecotourism and sustainability using a literature review and bibliometric analysis. The research conducted in this paper focused on intellectual structure, volume, knowledge development, the author and source impact. In this research, we will use Microsoft Excel, VOS Viewer Software, and R Studio to analyse databases and gather more information from Scopus. This study uses subjective measures to examine the connections between a resource, community, and tourism to evaluate the sustainability of ecotourism. We identify an increase in the volume of articles on ecotourism published in the last three years. Moreover, Ecotourism has recently grown at a rapid pace. The bibliometric study uses R to identify the subject's most influential journals, authors, and papers. This study also provides a key and crucial element of ecotourism and sustainability into a single concept.